Evaluating customer needs and the role of innovation management software in digital transformation consulting - Schomberg, Ellen Marie (2025)
This thesis explores the role of Innovation Management Software in enhacing digital transformation consulting, focusing on the fuzzy front end of innovatoin. By examining the challenges faces by organizations like Eviden, Siedle and Symrise, the study identifies key factors influencing innovation management practices. Through expert interviews and case studies, the research evaluates the potential of IMS to streamline idea management, foster collaboration, and align innovation afforts with strategic goals. The findings aim to provide actionable recommendation for Eviden strengthening client innovation processes, ensuring Eviden remains a leader in the digital transformation landscape.